Brevibacterium massiliense bacteremia. (2017) - Vecten, Maude; Gouriet, Frédérique; Cano, Aline; Raoult, Didier
Abstract: Brevibacterium massiliense infection in man is rare. We report here the second case with isolation of B. massiliense in human. This micro-organism requires specific laboratory investigations such as 16S rRNA gene sequencing for accurate species identification. The clinical outcome was favorable.